Vulnerabilidades y facilitación en el terremoto de abril 2016 Manabí - Aguilera Suárez, Verónica del Rocío (2018)
This essay shows how extreme natural events, such as earthquakes, constitute scenarios for exacerbating the situation of vulnerability of populations, but it also shows how the market and the State, facilitates certain power groups they settle in zones of seismic risk, due to the physical, landscape characteristics of the same. In the case of the April 2016 earthquake there was a type of vulnerability related to wealth, in terms of high-value real estate infrastructure in the market, tourist complexes and services created to serve these two sectors, and built in high-altitude areas. seismic risk. The concepts of vulnerability, marginalization and facilitation in Manabi cities affected by the earthquake are analyzed, based on Collins (2008), who states that, even when natural risks are thought to affect especially the poorest populations, there is a of vulnerability that affects the rich, through a mechanism called "facilitation", in which the State and the Market "facilitate" human settlements in risk areas. Another aspect that is analyzed is gentrification, which is a result of facilitation. With these categories of analysis, we look at the situation of Manabí around the 16 A earthquake, and how the market and the state allowed the expansion of the real estate and tourism industry in risk areas, displacing communities of traditional artisanal fishermen.